2022
DOI: 10.52082/jssm.2022.504
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Architectural and Force-Velocity Curve Adaptations following 10 Weeks of Training with Weightlifting Catching and Pulling Derivatives

Abstract: The aims of this study were to examine the muscle architectural, rapid force production, and force-velocity curve adaptations following 10 weeks of resistance training with either submaximal weightlifting catching (CATCH) or pulling (PULL) derivatives or pulling derivatives with phase-specific loading (OL). 27 resistance-trained men were randomly assigned to the CATCH, PULL, or OL groups and completed pre- and post-intervention ultrasound, countermovement jump (CMJ), and isometric mid-thigh pull (IMTP). Vastus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Although this approach may be novel, differences in subject training experience, technique, and anthropometrics may prevent its widespread use within the strength and conditioning field. As noted previously, weightlifting pulling derivatives are typically prescribed using percentages of a 1RM catching derivative (5,6,8,15,24,25,(27)(28)(29)(33)(34)(35). Although this may not be an issue if both weightlifting catching and pulling derivatives are prescribed, strength and conditioning practitioners only prescribing pulling variations may require a loading alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this approach may be novel, differences in subject training experience, technique, and anthropometrics may prevent its widespread use within the strength and conditioning field. As noted previously, weightlifting pulling derivatives are typically prescribed using percentages of a 1RM catching derivative (5,6,8,15,24,25,(27)(28)(29)(33)(34)(35). Although this may not be an issue if both weightlifting catching and pulling derivatives are prescribed, strength and conditioning practitioners only prescribing pulling variations may require a loading alternative.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the existing cross-sectional and longitudinal research on weightlifting pulling derivatives has primarily used percentages of a 1RM catching derivative to prescribe loads. For example, researchers have used loads based on the 1RM HPC or power clean of subjects to examine the differences between weightlifting catching and pulling derivatives (9,18,19,31,32,37,38,40,41) and the effect of load during different pulling derivatives (6,8,15,24,25,(27)(28)(29) as well as during training prescription (5,(33)(34)(35). Although prescribing loads in this manner may serve as an efficient strategy, these loads may not accurately represent the actual relative percentages of the exercise being performed.…”
Section: Introductionmentioning
confidence: 99%
“…compared with the HPC (13,40,46,49), especially at lighter loads (i.e., ,50% 1 repetition maximum [1RM] HPC). Despite the existing cross-sectional and longitudinal research on the JS and other weightlifting pulling derivatives, researchers have typically loaded these exercises based on the 1RM HPC or power clean of subjects when comparing different weightlifting exercises (6,15,18,41,45,49), examining the impact of different loads on performance (5,26,33,35), or during training prescription (2,(42)(43)(44). Although this may not be an issue when both weightlifting catching and pulling derivatives are prescribed, strength and conditioning practitioners must consider that loads based on another exercise may not accurately represent the relative loading percentages of a different exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Additional researchers examining the HEXJ concluded that PP occurred with loads ranging from 20–40% of a 1RM back squat [ 5 ] or 10–20% of a 1RM box squat [ 12 ]. Compared to the other two exercises, the JShrug is typically loaded using a percentage of a 1RM weightlifting catching derivative [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In this light, PP has been shown to be maximized between 30–45% of a 1RM hang power clean [ 14 , 16 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%